Imaging diagnosis of primary pelvic hydatid: a rare case report - Vaidya, Shirish V.; Patange, Neeraj A.; Khan, Sheeba J. (International Journal of Research in Medical Sciences, 2017)
Hydatid disease is caused by Echinococcus granulosus a commonly encountered parasitic infection to humans in tropical countries. Humans are accidental intermediate hosts of Echinococcus. Liver is the most commonly infected organ. Any organ of the body can be affected but primary pelvic hydatid disease is rarely reported. Preoperative diagnosis can be established by imaging studies such as ultrasonography, computed tomography (CT), and magnetic resonance imaging (MRI). Here, a case is reported of pelvic hydatid in a young female who presented with recurrent episodes of abdominal pain along with an abdominal mass. General physical examination and radiological evaluation confirmed a multiloculated cystic lesion in pelvic. Patient was subjected to laparotomy which confirmed the diagnosis of a primary pelvic hydatid disease.